Aqueous Phase Phosphorescence: Ambient Triplet Harvesting of Purely Organic Phosphors via Supramolecular Scaffolding. (29th November 2018) - Kuila, Suman; Rao, K. Venkata; Garain, Swadhin; Samanta, Pralok K.; Das, Shubhajit; Pati, Swapan K.; Eswaramoorthy, Muthusamy; George, Subi J.
Abstract: Ambient solution and amorphous state room temperature phosphorescence (RTP) from purely organic chromophores is rarely achieved. Remarkable stabilization of triplet excitons is realized to obtain deep red phosphorescence in water and in amorphous film state under ambient conditions by a unique supramolecular hybrid assembly between inorganic laponite clay and heavy atom core substituted naphthalene diimide (NDI) phosphor. Structural rigidity and oxygen tolerance of the inorganic template along with controlled molecular organization via supramolecular scaffolding are envisaged to alleviate the unprecedented aqueous phase phosphorescence. Abstract : Wässrige Phosphoreszenz : Ein Koassemblierungsansatz liefert organisch‐anorganische Hybride mit roter Phosphoreszenz sowohl im wässrigen als auch amorphen Zustand bei Raumtemperatur. Der Schweratomeffekt im Naphthalindiimid‐Derivat sowie dessen J‐Aggregation erhöhen die Effizienz des Intersystem‐Crossing, das starre und sauerstofftolerante Laponit‐Templat stabilisiert den Triplettzustand.